Exploring the potential of AI in tourism industry: combination TAM and innovation-decision process - Saowakhon Nookhao; Noppanon Homsud (Cogent Business & Management, 2025)
The rapid advancement of artificial intelligence (AI) has introduced transformative opportunities into the global tourism industry. However, the adoption of AI-driven services in tourism remains relatively limited, particularly in emerging markets such as Thailand. This study explores the key factors influencing the acceptance and adoption of AI-powered tourism services by integrating the Technology Acceptance Model (TAM) with the Innovation-Decision Process (IDP). A conceptual framework consisting of eight constructs–trust in AI, perceived ease of use, perceived usefulness, perceived value, perceived enjoyment, attitude towards use AI, intention to use, and actual use–was developed and empirically validated. Data were collected from 462 Thai tourists using a structured questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM). The results revealed that trust in AI and perceived ease of use are significant antecedents of perceived usefulness and attitude towards use AI, whereas perceived value and enjoyment positively influence attitude towards use AI. Attitude towards use AI and perceived usefulness subsequently affect intention to use, which in turn drives actual use behavior. By aligning TAM constructs with the corresponding stages of the IDP, this study contributes a novel framework for understanding the diffusion of AI innovations in tourism. These findings offer theoretical insights and practical implications for stakeholders aiming to promote sustainable and technology-enhanced tourism experiences in the next normal era.
Keywords: AI in Service Interactions; Digital Marketing and Social Media; Technology Adoption and User Behaviour